RETRACTED: Good Corporate Governance and Corporate Values with Profitability as a Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2012-2021 Period - Triono, Retno; Putra, Yudi Partama (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
RETRACTION NOTICE Following up on the review of articles published in Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan carefully, thoroughly, and considering the article entitled "Good Corporate Governance and Corporate Values with Profitability as a Moderating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2012-2021 Period" Vol. 4 No. 3 (2023): Juli, DOI: https://doi.org/10.37676/jhs.v9i2.4873 This paper was found to violate the publication principles of the Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan and has been withdrawn. This article has been withdrawn by the Author and the article withdrawal letter is attached in PDF form. The document and its contents have been removed from the Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, and reasonable efforts should be made to remove all references to this article.